Exploring in vivo placental microstructure in healthy and growth-restricted pregnancies through diffusion-weighted magnetic resonance imaging. (April 2020) - Andescavage, Nickie; You, Wonsang; Jacobs, Marni; Kapse, Kushal; Quistorff, Jessica; Bulas, Dorothy; Ahmadzia, Homa; Gimovsky, Alexis; Baschat, Ahmet; Limperopoulos, Catherine
Abstract: Introduction: Gross and microstructural changes in placental development can influence placental function and adversely impact fetal growth and well-being; however, there is a paucity of invivo tools available to reliably interrogate in vivo placental microstructural development. The objective of this study is to characterize invivo placental microstructural diffusion and perfusion in healthy and growth-restricted pregnancies (FGR) using non-invasive diffusion-weighted imaging (DWI). Methods: We prospectively enrolled healthy pregnant women and women whose pregnancies were complicated by FGR. Each woman underwent DWI-MRI between 18 and 40 weeks gestation. Placental measures of small (D) and large (D*) scale diffusion and perfusion ( f ) were estimated using the intra-voxel incoherent motion (IVIM) model. Results: We studied 137 pregnant women (101 healthy; 36 FGR). D and D* are increased in late-onset FGR, and the placental perfusion fraction, f, is decreased (p < 0.05 for all). Discussion: Placental DWI revealed microstructural alterations of the invivo placenta in FGR, particularly in late-onset FGR. Early and reliable identification of placental pathology in vivo may better guide future interventions. Highlights: Placental dysfunction can impact both maternal and fetal well-being. Histologic changes in placental development have been described in fetal growth restriction. Microstructural changes of the placenta remain difficult to identify in vivo Diffusion weighted magnetic resonance imaging is used to described in vivo microstructure. Small scale diffusion and the perfusion fraction of the in vivo placenta is reduced in fetal growth restriction.